Pengaruh Ketidaktentuan Lingkungan terhadap Penerapan Sistem Akuntansi Manajemen : Struktur Organisasi sebagai Faktor Moderasi - Kirmizi Ritonga; Yuserrie Zainuddin (The Indonesian Journal of Accounting Research, 2013)
This study examines the interactive effects of perceived environmental uncertainty and delegation and formalization on management accounting systems (MAS). MAS design is defined in terms of the extent to which managers use broad scope, timeliness, and aggregation in the condition of environmental uncertainty which is moderated by  delegating and formalization. The responses of 159 chief executive managers and senior managers, drawn from manufacturing companies of Indonesia, to a questionnaire survey were analysed by using a multiple regression technique. The result showed that the relationship between environmental uncertainty and information MAS aggregation were moderated by variables delegation and formalization.